Trends in HIV Prevalence and HIV-Related Risk Behaviors Among Male Students Who Have Sex With Men From 2016 to 2020 in Nanjing, China: Consecutive Cross-Sectional Surveys - Xu, Yuanyuan; Wu, Sushu; Fu, Xuezhen; Ding, Jie; Xu, Wenjiong; Li, Xin; Shi, Hongjie; Qiao, Mengkai; Zhu, Zhengping (Frontiers in Public Health, 2022)
Background The growing HIV epidemic among student men who have sex with men (MSM) necessitates immediate attention from public health. In China, male students who have sex with men (SMSM) were also at an increasing risk of HIV transmission. The aim of this study was to investigate the trends in HIV prevalence, HIV-related risk behaviors, and HIV testing, as well as analyze the factors associated with HIV infection among SMSM in Nanjing. Methods Data were collected through face-to-face questionnaire interviews and laboratory testing in Nanjing. The participants were recruited among SMSM by snowball sampling and internet-recruited convenience sampling annually from 2016 to 2020. The self-report data primarily included demographics, HIV knowledge, HIV-related behaviors, and HIV testing, while the laboratory test results of HIV and syphilis were collected. Linear-by-linear chi-square test was used to analyze the trends of HIV/syphilis prevalence and its risk behaviors. The binary logistic regression model was used to explore the factors associated with HIV infection. Results During the 5 years from 2016 to 2020, a total of 775 SMSM were recruited in our survey (220, 112, 171, 142, and 120, respectively). The HIV prevalence was 5.2, 6.3, 5.3, 7.0, and 8.3%, without a significant increasing trend (P = 0.277). Syphilis prevalence fluctuated from 5.7% in 2016 to 4.2% in 2020, without a significant decreasing trend (P = 0.318). The proportion of consistent condom use in anal intercourse (48.5 to 56.2%, P < 0.05), and HIV testing in the past 12 months (51.0 to 59.2%, P < 0.05) were increasing. A remarkable growing trend has been reported in the percentage of MSM with more than one male sex partner (46.2 to 59.2%, P < 0.05). Multivariate analysis showed that HIV testing in the past 12 months was a protective factor against HIV infection. MSM who had unprotected anal intercourse (UAI) in the past 6 months, recreational drug use, and currently syphilis infection were risk factors for HIV infection. Conclusions We observed stable HIV/ syphilis prevalence, increasing consistent condom use, increasing HIV testing rate, and increasing multiple male sex partners dramatically among SMSM in China. The original comprehensive intervention measures should be continuously strengthened for the subgroup. To satisfy the current HIV prevention requirements, new biological interventions should be introduced and carried out as major components of combination prevention programs.